Heat budget of the surface mixed layer south of Africa - Faure, Vincent; Arhan, Michel; Speich, Sabrina; Gladyshev, Sergey (Ocean Dynamics, 2011)
International audience ARGO hydrographic profiles, two hydrographic transects and satellite measurements of air-sea exchange parameters were used to characterize the properties and seasonal heat budget variations of the Surface Mixed Layer (SML) south of Africa. The analysis distinguishes the Subtropical domain (STZ) and the Subantarctic Zone (SAZ), Polar Frontal Zone (PFZ) and Antarctic Zone (AZ) of the Antarctic Circumpolar Current. While no Subantarctic Mode Water forms in that region, occurrences of deep SML (up to ∼450 m) are observed in the SAZ in anticyclones detached from the Agulhas Current retroflection or Agulhas Return Current. These are present latitudinally throughout the SAZ, but preferentially at longitudes 10-20° E where, according to previous results, the Subtropical Front is interrupted. Likely owing to this exchange window and to transfers at the Subantarctic Front also enhanced by the anticyclones, the SAZ shows a wide range of properties largely encroaching upon those of the neighbouring domains. Heat budget computations in each zone reveal significant meridional changes of regime. While air-sea heat fluxes dictate the heat budget seasonal variability everywhere, heat is mostly brought through lateral geostrophic advection by the Agulhas Current in the STZ, through lateral diffusion in the SAZ and through air-sea fluxes in the PFZ and AZ. The cooling contributions are by Ekman advection everywhere, lateral diffusion in the STZ (also favoured by the ∼10° breach in the Subtropical Front) and geostrophic advection in the SAZ. The latter likely reflects an eastward draining of water warmed through mixing of the subtropical eddies.